Entrevista com o professor Carlos Augusto de Figueiredo Monteiro - Armen Mamigonian; Leda Orselli; Maria Dolores Buss; Neide Oliveira de Almeida; Arlene Maria Maykot Prates (Geosul)
Entrevista com o professor Carlos Augusto de Figueiredo Monteiro